Visible wars, forgotten wars and world order. Media attention, cognitive competition and global response - Marsili, M. (Janus: Anuário de relações exteriores, 2026)
The current information environment has intensified competition for salience and widened the gap between what happens and what becomes visible. The unequal visibility of armed conflicts reveals a hierarchy of attention that is neither accidental nor politically neutral. Attention has material effects, not only affecting the behaviour of actors inside conflict zones but also with significant international consequences.